Girl in Pieces - Glasgow, Kathleen, 1969- (New York : Delacorte Press, 2016)
As she struggles to recover and survive, seventeen-year- old homeless Charlotte "Charlie" Davis cuts herself to dull the pain of abandonment and abuse.
Keywords: Emotional problems -- Fiction; Survival -- Fiction; Cutting (Self-mutilation) -- Fiction; Abandoned children -- Fiction; Sexual abuse -- Fiction; Homeless persons -- Fiction